2023
DOI: 10.1186/s12951-023-01822-5
|View full text |Cite
|
Sign up to set email alerts
|

Accelular nanofibrous bilayer scaffold intrapenetrated with polydopamine network and implemented into a full-thickness wound of a white-pig model affects inflammation and healing process

Abstract: Treatment of complete loss of skin thickness requires expensive cellular materials and limited skin grafts used as temporary coverage. This paper presents an acellular bilayer scaffold modified with polydopamine (PDA), which is designed to mimic a missing dermis and a basement membrane (BM). The alternate dermis is made from freeze-dried collagen and chitosan (Coll/Chit) or collagen and a calcium salt of oxidized cellulose (Coll/CaOC). Alternate BM is made from electrospun gelatin (Gel), polycaprolactone (PCL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…Also, the PDA microspheres with larger sizes on BC/PDA have a lower swelling rate than the surrounding BC gel, resulting in an overall lower swelling ratio for BC/PDA [ 48 , 49 ]. Similar results were reported by Kacvinska et al [ 50 ], who found that PDA coating of an implantable bilayer scaffold of collagen and chitosan (Coll/Chit) or collagen and a calcium salt of oxidized cellulose (Coll/CaOC) over electrospun gelatin, polycaprolactone, and CaOC affected swelling capacity and porosity.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Also, the PDA microspheres with larger sizes on BC/PDA have a lower swelling rate than the surrounding BC gel, resulting in an overall lower swelling ratio for BC/PDA [ 48 , 49 ]. Similar results were reported by Kacvinska et al [ 50 ], who found that PDA coating of an implantable bilayer scaffold of collagen and chitosan (Coll/Chit) or collagen and a calcium salt of oxidized cellulose (Coll/CaOC) over electrospun gelatin, polycaprolactone, and CaOC affected swelling capacity and porosity.…”
Section: Resultssupporting
confidence: 88%
“…Moreover, with an increase in the PDA concentration on the BC/PDA surface, there was an evident indication of more layers of cells than BC surfaces ( Figure 7 ). The higher number of cells in confluency could have arisen from the efficient adhesion and proliferation caused by the diffusion of nutrients through the pores of different layers of scaffolds [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have indicated that inflammation is an important differentiating factor in wound repair processes (42,43). Analyzing the key molecules in skin regeneration and inflammation revealed that the frequency of some keywords increased rapidly in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Coating is a drug-loading method that involves covering the surface of a scaffold with a drug or drug–carrier composite. To carry out the coating method, the drug must be dissolved in an appropriate solvent to prepare a drug solution [ 191 ]. An appropriate concentration for the drug solution can be selected based on the properties of the drug and scaffold.…”
Section: Nanofiber Scaffold Technologymentioning
confidence: 99%